LSPR detection of extracellular vesicles using a silver-PDMS nano-composite platform suitable for sensor networks. Issue 4 (20th April 2020) - Raju, D.; Bathini, S.; Badilescu, S.; Ouellette, R. J.; Ghosh, A.; Packirisamy, M.
ABSTRACT: A novel method for the detection of exosomes in body fluids and cell cultures has been developed. The method is an optical method, based on LSPR of silver nanoparticles. The method was extended to a microfluidic environment, amenable to be integrated in a sensor network. However, for clinical applications, their isolation, detection and quantification methods in bio-fluids are challenging. Herein, we present a simple label-free technique to capture and detect EVs, by using a synthetic peptide, called Vn96. To quantify EVs, a LSPR detection technique was used. This work is an attempt to adapt a biosensing method to the future requirements of Industry 4.0.